Phytochemical and Antimicrobial Activities of the Soapnut Saponin and its Derivatives from the Sapindus mukurossi - Rama Sekhara Reddy, D.; Mallika, D.; Damodar Reddy, G.; Murthy, Y.L.N. (Asian Journal of Chemistry, 2010)
The phytochemical study of the soapnuts of Sapindus mukurossi revealed the presence of saponins from water extract. The saponins and its derivatives are identified based on their melting points, IR, 1H and 13C NMR spectral data, as saponin, saponin acetate, saponin methyl ester, saponin methyl ester acetate, hederagenin. The antimicrobial activities of the saponin and its derivatives were investigated. The saponin and its derivatives were tested for their antibacterial activities against gram positive, gram negative organisms and fungi.